Antioxidant dietary approach in treatment of fatty liver: New insights and updates - Ferramosca, Alessandra; Di Giacomo, Mariangela; Zara, Vincenzo (World journal of gastroenterology : WJG, 2017)
Non-alcoholic fatty liver disease (NAFLD) is a common clinicopathological condition, encompassing a range of conditions caused by lipid deposition within liver cells. To date, no approved drugs are available for the treatment of NAFLD, despite the fact that it represents a serious and growing clinical problem in the Western world. Identification of the molecular mechanisms leading to NAFLD-related fat accumulation, mitochondrial dysfunction and oxidative balance impairment facilitates the development of specific interventions aimed at preventing the progression of hepatic steatosis. In this review, we focus our attention on the role of dysfunctions in mitochondrial bioenergetics in the pathogenesis of fatty liver. Major data from the literature about the mitochondrial targeting of some antioxidant molecules as a potential treatment for hepatic steatosis are described and critically analysed. There is ample evidence of the positive effects of several classes of antioxidants, such as polyphenols ( ., resveratrol, quercetin, coumestrol, anthocyanins, epigallocatechin gallate and curcumin), carotenoids ( ., lycopene, astaxanthin and fucoxanthin) and glucosinolates ( ., glucoraphanin, sulforaphane, sinigrin and allyl-isothiocyanate), on the reversion of fatty liver. Although the mechanism of action is not yet fully elucidated, in some cases an indirect interaction with mitochondrial metabolism is expected. We believe that such knowledge will eventually translate into the development of novel therapeutic approaches for fatty liver.